(untitled) (Revista de Ciências Agroveterinárias, 2019)
This study aimed to evaluate the performance of goats grazing black oat (Avena strigosa) fed with different levels of supplementation as well as its influence on soil resistance to penetration and corn yield grown in succession with increasing levels of N top dressing. In the winter, ten month‑old Boer goats received supplementation levels at 0, 5, 10, and 15 g kg-1 of body weight, in continuous stocking grazing, with variable stocking rate, and with a control without grazing. In the summer, the main plots were divided into sub-plots and N was applied at increasing levels in top dressing on the corn crop (0, 50, 100, and 150 kg ha-1 of N as urea). In the winter, the forage sward mass and its forage production, stocking rate, animal live weight gain and soil resistance to penetration were evaluated. In the summer, the corn yield components were evaluated. Stocking rate increased as supplement levels increased, which also increased the intensity of trampling and hence the resistance to soil penetration in the surface layer without affecting the grain yield of the corn grown in succession. When winter grazing is in accordance with the forage height and the fertilization, it reduces the need for nitrogen in the summer to obtain the corn yield produced in ungrazed areas in the winter.